Sturm-Liouville difference equations having Bessel and hydrogen atom potential type - Bas, Erdal; Ozarslan, Ramazan; Baleanu, Dumitru (De Gruyter Poland Sp Zoo, 2018)
In this work, we bring a different approach for Sturm-Liouville problems having Bessel and hydrogen atom type and we provide a basis for direct and inverse problems. From this point of view, we find representations of solutions and asymptotic expansions for eigenfunctions. Furthermore, some numerical estimations are given to illustrate the necessity of the Sturm-Liouville difference equations with the potential function for the convenience to the spectral theory. The behavior of eigenfunctions for the Sturm-Liouville problem having Bessel and hydrogen atom potential type is analyzed and compared to each other. And then, comparisons are showed by tables and figures.
Keywords: Sturm-Liouville; Difference equation; Bessel potential; Hydrogen atom potential; Schrodinger equation